Effect of transmittance reduction on performance of flat-plate solar collector when increasing covers number using "TRNSYS" program - Alsakit, Warda; Azzain, Gassem (Journal of Pure & Applied Sciences, 2023)
The transmittance of a flat-plate solar collector decreases when the number of its covers are increased, and its performance rates change accordingly. This paper presents the process of verifying this through a set of comparisons that include the efficiency of the solar collector, the temperature of the outlet water, and the amounts of heat energy gained and lost from this collector when it is provided with one cover, two covers, and three transparent covers. The digital simulation was conducted on a simple solar domestic water heating system using TRNSYS software. Dynamic simulations demonstrated that increasing the number of transparent covers resulted in a significant decrease in the optical efficiency of this collector due to the reduction of transmittance. Although this procedure has limited the total heat loss by radiation, convection, and conduction. However, in general, there was a continuing trend of declining overall efficiency as a result of the increase in the number of covers.